Faktor-faktor yang Memengaruhi Kepatuhan Budaya K3 dan Risiko Infeksi Terkait Laboratorium (LAIs) di Indonesia: Literature Review - Wau, Herbert; Hartono, Hartono; Silalahi, Ananta Juliana Cindy (SENTRI: Jurnal Riset Ilmiah, 2026)
Background: Medical laboratories represent high-risk working environments for Laboratory-Acquired Infections (LAIs) due to daily interactions with infectious specimens. In Indonesia, this challenge is compounded by a high burden of infectious diseases and gaps between occupational safety regulations and field practices. Objective: This study aims to analyze the factors influencing infectious disease transmission among laboratory workers in Indonesia and evaluate the effectiveness of compliance with safety standards. Method: This study utilized a Literature Review method following the PRISMA 2020 guidelines. Literature searches were conducted across Google Scholar, PubMed, ResearchGate, and Garuda databases for original research articles published between 2017 and 2026. A total of 15 selected articles were synthesized narratively. Results: The primary factors identified include the level of compliance in using Personal Protective Equipment (PPE), knowledge and attitudes toward Standard Operating Procedures (SOPs), as well as management factors such as training and supervision. Inappropriate use of PPE and unsafe practices, such as manual needle recapping, emerged as critical risks for transmission. Conclusion: The risk of infection transmission is multifactorial, encompassing individual, behavioral, and work environment elements. Strengthening a safety culture supported by PPE logistical backing and strict supervision is essential to protect laboratory personnel.